Men's grooming in Germany: a consumer research and discussion of current consumer attitudes - Borger, Greta Philine (2015)
The objective of this dissertation was to explore the German men’s grooming market and to discuss the usage and purchase behavior of young male adults. After a brief market analysis, this dissertation evaluates the results of qualitative and quantitative research. The conducted research explored the consumer’s reasoning for and attitude towards personal grooming, and their attitude towards product attributes and the aging process. The dissertation concludes that men attach high value to personal grooming but only to the extent that their personal need is satisfied. As the male involvement in MG is highly dependent on each consumer’s individual needs, the market requires a careful segmentation.